2020
DOI: 10.1093/milmed/usz447
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research and Practice Collaborative: An Evidence-Based Nursing Clinical Inquiry Expansion

Abstract: Introduction: Implementation and sustainment of evidence-based practices (EBPs) are common challenges faced by healthcare organizations. The Clinical Research and Practice Collaborative, an evidence-based initiative implemented at a large Military Treatment Facility, addresses EBP implementation and sustainment by expanding the culture of nursing clinical inquiry and broadening nursing research efforts to include EBP. The evidence-based intervention of scheduled, intentional, intraprofessional collaboration be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
8
1
1
Order By: Relevance
“…This information calls for future directions to help nurses build and maintain research skills. The finding is inconsistent with the work of Lehane et al (2019) and Migliore et al (2020) which reported a high level of clinical research competencies among nurses.…”
Section: Leadership Competencies Of First-line Nurse Managerscontrasting
confidence: 87%
“…This information calls for future directions to help nurses build and maintain research skills. The finding is inconsistent with the work of Lehane et al (2019) and Migliore et al (2020) which reported a high level of clinical research competencies among nurses.…”
Section: Leadership Competencies Of First-line Nurse Managerscontrasting
confidence: 87%
“…Migliore et al. (2020) also stress the importance of cooperation between science and advanced clinical practice for establishing EBP in nursing, while Oh et al. (2016) found that before implementing an EBP initiative, systematic educational programmes that target EBP mentors should be offered.…”
Section: Implication For Nursing Managementmentioning
confidence: 99%
“…Therefore, a facilitator for such activities is a nurse scientist salary that is supported in the organizational budget to provide time for this work (Logsdon et al, 2017). Other reported facilitators of the nurse scientist role involve institutional support for: Nursing research and EBP committees or councils (Birkhoff et al, 2020; Granger, Westlak, et al, 2021; Siedlecki & Albert, 2020); EBP process model for implementation and outcomes (Chesak et al, 2020; Migliore et al, 2020); Institutional champions for research and EBP (Vessey et al, 2017); Fellowship or Clinical Scholars programs in EBP and research to increase outcomes and develop staff (Brant, 2015; Carter et al, 2020; Granger, Bryant, et al, 2021; Milne et al, 2007; Mulvenon & Brewer, 2009; Schwartz, 2014; Siedlecki & Albert, 2020); Institutional infrastructure supporting EBP implementation and research, grant writing, and securing funds (Grange et al, 2005; Granger, Westlak, et al, 2021); and Software and technology platform access to collect and analyze data (Hickey, 2018). …”
Section: Resultsmentioning
confidence: 99%